PENGARUH PENURUNAN HARGA KARET MENTAH TERHADAP DAYA BELI MASYARAKAT DI PASAR DESA PASIR JAYA - Yulfita A’ini, Wirdatul Jannah (Jurnal Ilmiah Cano Ekonomos, 2016)
This research was conducted to analyze the effect go down price of raw rubber to power of buy society at traditional market in Pasir Jaya village. This research was conductedusingquantitative data,data collectionin this study usinga questionnaire containing20grains ofquestions and distributed to85respondents who had income from the sell of raw rubber. The sampling techniquethat researchers dothat isto use the formulaslovin. Analysis ofdata usedin this studyistotest hypothesesusing validityand reliability testing. The results of theregression analysisindicatethere is a verystrongand significant correlation between go down price of raw rubber with power of buy society at traditional market in Pasir Jaya village that is equal to 0,529 or by 52,9%. Researcher is recommended to society at Pasir Jaya village to be more high the quality of the raw rubber so that the power of sale the raw rubber have a high level or the society must have a side job so that the society have a other income.